Enhancing Amarath Growth and Yield in Kabale District. - Tumwine, David (Kabale University, 2024)
Amaranth, a highly nutritious and versatile crop, has emerged as a promising solution to food security and malnutrition challenges, particularly in regions like Kabale District in Uganda. This study aimed to enhance amaranth yield and usage in Kabale by investigating the impact of different manure types on crop performance, optimizing agronomic practices, and addressing local food security issues. Conducted over six months (January to June 2024) in Kikungiri Hill, Kabale Municipality, the research focused on the effects of organic and inorganic manures on amaranth growth, yield, and quality. Experimental results demonstrated that inorganic manure (DAP) significantly outperformed organic manure (cow dung) and control treatments in terms of plant height, number of leaves, and grain yield. Specifically, inorganic manure yielded the highest average grain output of 8.6 kg, compared to 7.9 kg for organic manure and 6.0 kg for the control. The study underscores the critical role of optimal manure application in enhancing amaranth productivity and proposes recommendations for farmers and policymakers, including the adoption of DAP fertilizer and further research on alternative manure types and amaranth varieties. By improving nutrient management and agronomic practices, this research contributes to sustainable agriculture and food security efforts in Kabale District.